Stage and outcomes of invasive cervical cancer patients in Botswana: A prospective cohort study from 2013 to 2020 - Surbhi Grover; Jessica George; Shawna Tuli; Katie Lichter; Rohini Bhatia; Barati Monare; Ganen Chinniah; Lisa Bazzett-Matabele; Memory Bvochora-Nsingo; Sebathu Chiyapo; Dawn Balang; Tlotlo Ralefala; et al. (Elsevier, 2022)
Objective: To present the stage distribution, patterns of care, and outcomes of patients from Botswana with invasive cervical cancer, living with or without HIV. Methods: Between 2013 and 2020, women with cervical cancer were prospectively enrolled in an observational cohort study. Results: A total of 1,043 patients were enrolled; 69% were women living with HIV. The median age of the cohort was 47 years (interquartile range [IQR] 40-58 years), with women living with HIV presenting at a younger age compared to women without HIV (44 versus 61 years, p < 0.001). Among women living with HIV, the median CD4 count at the time of cancer diagnosis was 429.5 cells/μL (IQR 240-619.5 cells/μL), 13% had a detectable viral load, and 95% were on antiretroviral therapy. In regard to treatment, 6% (n = 58) underwent surgery, 33% (n = 341) received radiation therapy, 51% (n = 531) received chemoradiation, and 7% (n = 76) did not receive treatment. Stage distribution in the cohort was as follows: I 17% (n = 173), II 37% (n = 388), III 35% (n = 368), and IV 8% (n = 88). For all patients, 2-year OS was 67%. In multivariable Cox regression, worse OS was associated with stage: II (HR 1.91, p = 0.007), III (HR 3.99, p < 0.001), and IV (HR 5.06, p < 0.001) compared to stage I. Improved OS was associated with hemoglobin > 10 g/dL (HR 0.51, p < 0.001) compared to Hb ≤ 10 g/dL. Conclusions: Among women in Botswana with cervical cancer, most patients presented with stage II or III disease warranting radiation therapy or chemoradiation. While two-thirds of cervical cancer patients were women living with HIV, HIV did not impact OS.